Physics of interactions at biological and biomaterial interfaces - Tanaka, Motomu (Current opinion in colloid & interface science, 2013)
Soft interlayers based on membranes and biopolymers define the spatial boundaries between different phases in biological systems. Physical interactions of soft matter under biologically relevant conditions (in aqueous media containing various ions) are governed by complex interplays of generic and specific interfacial interactions, which are clearly different from those acting at the interface between hard matter. This review aims at providing a comprehensive overview on: (a) models of cell-cell and cell-tissue interfaces with aid of defined building blocks, (b) new X-ray and neutron scattering techniques to probe fine structures, electrostatics, and mechanics of soft interfaces, and (c) control of dynamic cell morphology and migration of cells using tailor-made, soft interfaces.
Gesehen am 31.01.2022